Diet and Immune Function - Childs, Caroline E (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Supporting initiation, development and resolution of appropriate immune responses is key to survival. Many nutrients and dietary components have been purported to have a role in supporting optimal immune function. This is vital throughout the life course, from the development and programming of the immune system in early life, to supporting immunity and reducing chronic inflammation in older people. In this special issue of Nutrients, we examine the evidence for the role of diet and dietary components in promoting protective immunity.